A comparative evaluation of the effect of various chelating agents on the microhardness of root canal dentin: An in vitro study - Mineet Kaul; Zinnie Nanda; Kranthikumar Reddy; Rahul Deore; Divya Mandlecha; Esha Jaiswal (Wolters Kluwer Medknow Publications, 2023)
Aim: The aim of this study was to evaluate and compare the effect of 17% liquid ethylenediaminetetraacetate (EDTA), 10% citric acid, and 9% 1-hydroxy ethylidene-1,1-bisphosphonate (HEBP) on the microhardness of root canal dentin. Materials and Methods: Eighteen mandibular premolars which were freshly extracted were selected and randomly assigned to one of the three groups (n = 6). After decoronating, the teeth at the cementoenamel junction, specimens were prepared up to F3 (ProTaper Universal). After each instrument, irrigation was done with 3% sodium hypochlorite. Specimens were sectioned longitudinally to expose dentin surface and mounted on acrylic resin blocks. One half served as the test group and the other served as its control. The dentin was covered with test solutions throughout its length for 5 min. Group 1: 17% liquid EDTA, Group 2: 10% citric acid, and Group 3: 9% HEBP. Measurement of microhardness was done using Vickers indenter at 1000 μm, 1200 μm, 1400 μm from orifice of root canal and 100 μm from pulp-dentin junction, a load of 50 g for 15 s dwell time was applied. A mean of the three readings was used to calculate microhardness. Statistical analysis was performed using one-way ANOVA and post-hoc Tukey test at P ≤ 0.05. Results: The mean microhardness of EDTA reduced from 52.28 VHN to 39.00 VHN, and that of citric acid reduced from 52.50 VHN to 47.30 VHN, whereas, HEBP showed least reduction, from 52.46 VHN to 50.52 VHN. Conclusion: A reduction in microhardness was evident on using all three chelating agents. However, HEBP caused the least reduction in microhardness and can be a potential chelating agent for use in endodontics.